Chromium Contamination in Vegetable's Samples Irrigated Through Different Water Sources - Shaheen, Qamar; Mahmood, Zaid; Imran, Muhammad; Robina Gillani, Syeda; Ahmed Faridi, Ilyas (Asian Journal of Chemistry, 2011)
This work evaluates the effects of water of irrigation in comparison with the source of water with special reference to chromium contamination in vegetables grown in various areas of Pakistan. Twenty samples of each vegetable, i.e., spinach (Spinacia oleracea), lettuce (Lactuca sativa), carrot (Daucus cariota), capsicum (Capsicum fistulosus), sweet pea (Lathyrus odoratus), potato (Solanum tuberosum) and cabbage (Brassica oleracea), were collected during the year 2006 and replicated in 2007 and 2008. The range of concentration of chromium in vegetables irrigated with tube well water, canal water and municipal sewage water was in between 0.3-5.3, 1.01-13.09 and 1.11-29.89 ppm, respectively. Statistical analysis shows that the vegetables grown by tube well water and canal irrigation are quite safe and show less than 1 % samples of vegetables showing chromium concentration more than that of permissible ambient levels. In case of vegetables irrigated by municipal sewage water more than 50 % samples contained Cr more than that of permissible ambient levels. The results reflect that the uptake of chromium in vegetables is facilitated under the condition where the source of irrigation is sewage water.